PENGARUH KEPEMILIKAN INSTITUSIONAL, STRUKTUR MODAL, PROFITABILITAS, DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2014-2016) - ISNAINI FITRIA RAHMAWATI, 14.05.51.0168; Taswan, Taswan (Students' Journal of Economic and Management, 2018)
the value of the company is the perception of investor toward the company, which is often linked to the share price. The high share price makes the value of a company is also high.the stock price is the price that occurs when stock in trade in the market, this study only examined four variable, which are institutional ownership, capital structure, profitability and firm size. The purpose of this study is to find out the influence of institutional ownership, capital structure (DER), profitability (ROA) and firm size (Total Aset) on value of company. The sampel was manufacturing companies listed on the Indonesia Stock Exchange on period of 2014-2016 as much as 36 companies by using purposive sampling method. Methods of analysis used was multiple linear regression analysis using SPSS program. The result showed the institutional ownership and profitability affect the value of the company, while the capital structure and firm size does not affect the falue of company. Keywords : institutional ownership, capital structure, profitability, firm size